Gender effect on non-motor symptoms in Parkinson's disease: are men more at risk?. (February 2017) - Nicoletti, A.; Vasta, R.; Mostile, G.; Nicoletti, G.; Arabia, G.; Iliceto, G.; Lamberti, P.; Marconi, R.; Morgante, L.; Barone, P.; Quattrone, A.; Zappia, M.
Abstract: Introduction: Several gender differences have been reported in Parkinson's Disease (PD). We evaluated the burden of non-motor symptoms (NMS) in PD and the possible gender differences in their occurrence. Methods: The FRAGAMP study is a large multicenter case-control study. PD patients and controls underwent a face-to-face interview and a neurological examination performed by trained neurologists. Presence of NMS was investigated using a standardized questionnaire; cognitive impairment and depression were assessed using the Mini Mental State Examination and the Hamilton Depression Rating Scale respectively. Results: 585 PD patients (59.5% men) and 481 controls (34.9% men) were enrolled in the study. All NMS were significantly more frequent among PD patients than controls. PD women showed a significantly higher frequency of depression and urinary disturbances than parkinsonian men; a close frequency among PD women and men was recorded for hallucination, cognitive impairment and sleep disorders. Nonetheless, with respect to the control population, according to logistic regression stratified by sex and adjusted by age, PD men showed a stronger positive significant association with almost all NMS compared to women, excepting for urinary disturbances. The strongest association among PD men was recorded for cognitive impairment (adjusted OR 5.44 for men and 2.82 for women) and depression (adjusted OR 30.88 for men and 12.72 for women). Conclusions: With respect to the general population, presence of NMS was stronger associated with male gender. Our data suggest that the presence of NMS among PD men is more strictly due to the neurodegenerative processes related to PD. Highlights: We evaluated the burden of non-motor symptoms (NMS) in PD and the possible gender differences in their occurrence. 585 PD patients and 481 age-matched controls underwent a face-to-face interview and a neurological examination. All NMS were significantly more frequent among PD patients than controls. With respect to controls, PD men showed a stronger positive significant association with almost all NMS compared to women. The presence of NMS in PD is more related to neurodegeneration than ageing and the risk of NMS in PD is greater for men.